'The Going Out of the Voluntary and the Coming in of the Compulsory': The Impact of the 1838 Irish Poor Law on Voluntary Charitable Societies in Dublin City. (December 2018) - McCabe, Ciarán
The introduction of the workhouse-centred Poor Law system into Ireland on the eve of the Great Famine transformed the provision of poor assistance in the country. Throughout various urban centres, the plethora of charitable societies that had been prominent in the provision of corporate assistance to the poor faced an increasingly uncertain future, fearing that the levying of compulsory poor rates would result in a withdrawal of support from subscribers and donors. This article analyses the impact of the Poor Law system on charitable societies in Dublin city, covering the fifteen-year period between the 1830 Select Committee on the State of the Poor in Ireland to the eve of the Great Famine in 1845. The article outlines how the establishment of the statutory Poor Law system resulted in confusion among the managers of existing welfare institutions and demonstrates that the opening of Poor Law Union workhouses greatly affected charitable societies' pauper lists and income levels; yet the impact on the many charities that dotted Dublin's crowded welfare landscape was not uniform.